Criteria of Recovery of Reproductive Health in Women With Chronic Inflammatory Processes of Genitals - Tanko, O. P.; Gaponova, L. O.; Samoylova, M. V. (Problems of Cryobiology and Cryomedicine, 2008)
Contemporary principles of treatment for patients with chronic inflammatory processes of uterine appendages have been considered. On the base of studying the clinical, immunological and rheological indices for the patients there was developed and introduced into clinical practice pathogenetically substantiated therapeutic method, contributing to the improvement of the parameters of regional hemodynamics, immunological status, as well as rapid elimination of pain syndrome.